2014
DOI: 10.1016/j.febslet.2014.02.033
|View full text |Cite
|
Sign up to set email alerts
|

The C‐terminal region of Xpc is dispensable for the transcriptional activity of Oct3/4 in mouse embryonic stem cells

Abstract: a b s t r a c tThe transcription factor Oct3/4 is essential to maintain pluripotency in mouse embryonic stem (ES) cells. It was reported that the Xpc DNA repair complex is involved in this process. Here we examined the role of Xpc on the transcriptional activation of the target genes by Oct3/4 using the inducible knockout strategy. We found that the removal of the C-terminal region of Xpc, including the interaction sites with Rad23 and Cetn2, showed faint impact on the gene expression profile of ES cells and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 24 publications
2
9
0
Order By: Relevance
“…Using an inducible knockout strategy, Niwa and coworkers recently reported that XPC may be dispensable for mESC pluripotency and O/S transcription, and that its loss has a modest impact on global gene expression, as measured by microarray analyses (41). This finding is in agreement with previous studies showing that Xpc knockout mice are viable with no overt developmental defects, although they are UV sensitive (42,43).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Using an inducible knockout strategy, Niwa and coworkers recently reported that XPC may be dispensable for mESC pluripotency and O/S transcription, and that its loss has a modest impact on global gene expression, as measured by microarray analyses (41). This finding is in agreement with previous studies showing that Xpc knockout mice are viable with no overt developmental defects, although they are UV sensitive (42,43).…”
Section: Discussionsupporting
confidence: 83%
“…S5). It is also worth pointing out that in Ito et al (41), floxing the Xpc gene reduces its mRNA level by half even before Cre excision; in these Xpc fl/fl ESCs, Nanog transcripts are reduced compared with WT cells as much as we observe upon SCC depletion. These results taken in aggregate suggest that, although SCC might be dispensable for mESC self-renewal and pluripotency because of partial functional redundancy, SCC remains an important player in stabilizing stem cell transcriptional programs.…”
Section: Discussionsupporting
confidence: 60%
“…Arguably, the functional role of XPC in stem cell pluripotency contrasts with the lack of any apparent developmental defects seen in Xpc −/− mice . It is also puzzling that ablation of the C‐terminal region of Xpc gene abrogating the interaction sites of XPC with RAD23 and CETN2 has minimal impact on gene expression . More importantly, the truncated Xpc embryonic stem cells retain proper gene expression patterns and pluripotency to contribute chimeric embryos .…”
Section: Linking Ner To Transcription Demandsmentioning
confidence: 99%
“…It is also puzzling that ablation of the C‐terminal region of Xpc gene abrogating the interaction sites of XPC with RAD23 and CETN2 has minimal impact on gene expression . More importantly, the truncated Xpc embryonic stem cells retain proper gene expression patterns and pluripotency to contribute chimeric embryos . Thus, the true biological relevance of XPC in developmental gene expression programs remains elusive.…”
Section: Linking Ner To Transcription Demandsmentioning
confidence: 99%
“…It has been shown that XPC physically interacts with RAD23B and CETN2 to form a tight complex, which was reported to function as an OCT4/SOX2 coactivator to enhance expression of pluripotency genes such as NANOG in ES cells (34 -36). However, a follow-up study has shown that inducible knockout of the XPC C-terminal region, which contains the interaction sites with RAD23B and CETN2, has no impairment on OCT3/4 transcriptional activity and the maintenance of pluripotency (37), casting doubt on the coactivator role of XPC. The intriguing roles of XPC in nucleotide excision repair and potentially in transcriptional regulation prompted us to examine the level of XPC protein in multilineage differentiation of NT2 cells.…”
Section: Up-regulation Of Xpc Protein and Enhancement Of Uv Resistancmentioning
confidence: 99%